UPAH SULAM BIBIR DAN ALIS PERSPEKTIF HUKUM ISLAM - Moh. Sholehuddin (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2016)
The research data were collected through the views of scholars of the act changing God's creation, the views of scholars associated with Qiya>s, Islamic views pertaining to ingredients halal and haram, and the views of medical experts to the effects of the lip and eyebrow embroidery. Then analyzed with descriptive analysis techniques. The study concluded that the lip and eyebrow embroidery is haraam for two reasons. First, lip and eyebrow embroidery is an act (ornate) excessively that this act hated God. As word of Allah in Surah al-A'raf paragraph 31: